PENYELESAIAN SENGKETA PERBATASAN LAUT ANTARA PERU DENGAN CHILE MELALUI MAHKAMAH INTERNASIONAL TAHUN 2008-2014 - Citra Suryani; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the efforts made in the settlement of the maritime boundary disputebetween Peru to Chile. Respective claims began in 1947, in which States claims jurisdiction andexclusive rights to waters along 200 miles of the coast respectively. Then the two countries, Peruand Chile, as well as Ecuador, in the 1950s into a different agreement on maritime zones.Official legal dispute began in 2007 when Peru certify a graph showing that the claimed seaarea overlaps with areas claimed by Chile. Negotiations have been conducted by both parties inresolving the problems that occur in the border starting from the 1960s. But efforts to negotiatein terms of determining the maritime boundary between Peru definite and Chile did not succeed,because the two countries have different interpretations of the border. Last negotiation effortsundertaken by Peru expressly rejected by Chile. Peru finally decided to resolve this disputelegally through the International Court of Justice (ICJ).Keywords: Maritime Dispute, international Treaty, Delimitation, ICJ